The New South - West, Georgiana (My University, 1907)
Introduction: "The New South"; The phrase is enormously popular. It is a prime favorite with newspapers, magazines and politicians. Public speakers employ it to adorn their most aspiring periods". The last applies principally to Southern orators speaking at Northern banquets. It seems to be admitted that a new South must be made and not a modified old one. Everything must be new; the character of the South, its principals and its institutions. The South, as it is to day, is very differnet from what the South was at the begining of the Civil War, and very many of the changes are for the better. That slavery abolition was a great thing for the country need not be said as it has been proven in scores of ways. It was a most, remarkable change and different from any evolution in the history of any people. The people accept the result and are doing all in their power to adjust, satisfactorily, the relations between the former master and his slaves and to redistribute the landed property. There have not been enough people in the South to work the immense plantations and the conditions have been very bad. However, for this trouble there is immediate relief. Heretofore the tide of immigration, coming to this country has gone to the North and North west. There have been millions and millions who have gone there but those that went to the South could be counted by the hundreds. Capital and investment also avoided and distrusted the South. But in the last few years the people who have been up in the colder parts have discovered…
Citation: West, Georgiana. The New South. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: The American South; The South; The Post-Civil War South; Changes in the South; Theses